Keterlambatan Pengumpulan Berkas Verifikasi Klaim BPJS di RS X: Apa Akar Masalah dan Solusinya? - Estri Aditya Pradani; Dewi Lelonowati; Sujianto Sujianto (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to analyze root problems and the best solution of entry delays in the BPJS claim verification file to IJP (Installation of Financing Guarantee) of the hospital. This research is a qualitative descriptive research using Focus Group Discussion, Fishbone diagram and “5 Why” question methods to find the root problems. After that, the choice of alternative solutions is determined by Nominal Group Technique (NGT) and Capability Accessibility Readiness and Leverage (CARL) methods. This activity involves 2 management staffs, 3 IJP staffs, 2 pharmacists, and 7 nurses from emergency department, outpatient and inpatient units. The result of this research is written feedback by IJP for all outpatient and inpatient unit as the best solution which is expected to overcome the entry delays problem.